2021
DOI: 10.3390/agronomy11122520
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Growth and Development of Sclerotinia sclerotiorum (Lib.) De Bary by Combining Azoxystrobin, Penicillium chrysogenum VKM F-4876d, and Bacillus Strains

Abstract: Sclerotinia sclerotiorum (Lib.) de Bary is a plant pathogen with a wide host range, which causes significant yield and storage losses of edible roots and other plant products. Due to its ability to sclerotia formation, the efficient control of this pathogen is complicated. The study of five Bacillus strains (B. subtilis VKM B-3154D, VKM B-3155D, VKM B-3505D, VKM B-2998D, and B. amyloliquefaciens VKM B-3153D) showed their ability to produce polyene antibiotics suppressing the growth and development of plant pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Earlier, we determined the DMP ability to suppress the growth of Sclerotinia sclerotiorum (Lib.) de Bary [44], some pathogenic Fusarium fungi (Fusarium oxysporum, F. graminearum, F. avenaceum, and F. culmorum) [31], and Alternaria solani [45] when used both individually and in combination with some fungicides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, we determined the DMP ability to suppress the growth of Sclerotinia sclerotiorum (Lib.) de Bary [44], some pathogenic Fusarium fungi (Fusarium oxysporum, F. graminearum, F. avenaceum, and F. culmorum) [31], and Alternaria solani [45] when used both individually and in combination with some fungicides.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we identified 6-demethylmevinolin, or mevastatin, as a component of the culture broth of F-4856D [44]. This compound possesses antifungal properties due to its ability to inhibit the biosynthesis of ergosterol, a basic cell wall component in fungi [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…DMP obtained from VKM F-4876D has been previously shown to suppress the growth and development of Sclerotinia sclerotiorum (Lib.) de Bary [31] and several plant pathogenic Fusarium fungi (F. oxysporum, F. graminearum, F. avenaceum, and F. culmorum) [30] when used both alone and in combination with azoxystrobin. The current study showed that DMP also possesses a significant antifungal activity against A. solani.…”
Section: Discussionmentioning
confidence: 99%
“…The past study showed the ability of this strain to suppress the growth and development of Sclerotinia sclerotiorum (Lib.) de Bary and plant pathogenic Fusarium fungi (F. oxysporum, F. graminearum, F. avenaceum, and F. culmorum) under the conditions of both the combination of a dry mycelium biomass (DMP) of P. chrysogenum F-4876D with azoxystrobin and the use of DMP only [30,31]. Thus, taking into account the significance of potato as an agricultural crop in Russia and on a global scale, it was interesting to study the antifungal activity of DMP, used alone or in combination with several commercial fungicides (azoxystrobin-, tebuconazole-, fludioxonil-, and difenoconazole-based formulations used for potato protection) to control A. solani.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this impedes mycelial growth and serves as a preventive measure against the development and proliferation of pathogenic spores [13]. It is able to block the development of ascospores that can be considered as an indirect way to control S. sclerotiorum spreading, since sclerotia, which provides the development of the apothecium and ascospores, may initiate new disease development cycles, thus complicating the control of this pathogen [14]. It can also be used to control Ascochyta, Powdery mildew, and other diseases transmitted through the foliar and soil [15].…”
Section: Introductionmentioning
confidence: 99%